Pemberdayaan dan Pendampingan Masyarakat Desa dalam Transformasi Digital Pelayanan Publik Berbasiskan Website - Ari Sulistyanto; Pagi Muhamad; Dwinarko Dwinarko; Tabrani Sjafrizal (Jurnal Pengabdian Masyarakat (ABDIRA), 2022)
Digital transformation in the village can accelerate the community's welfare. However, until now it is still rare to use digital-based media, especially in public services. Therefore, there is a need for a socialization program, website-based digital infrastructure, and training on the operation of digital platforms in public services. The implementation method starts from the preparation stage, identifying the scope of public services, making website designs, uploading on the internet digital platform, website socialization, and training. The result of the activity is the availability of the Ponggang Village Website page using the Google Site as a public service facility. The Ponggang Village government apparatus is aware of the importance of using digital platforms in service to the community. Operating a digital platform in the form of a website, it shows that village apartments can be practiced well. These results show that the village government and the people of Ponggang Village have a high awareness of using digital platforms to support activities, especially in public services.